Determining the Efficiency Indicators of Excavators in Open-Pit Mining Processes at Mining Enterprises (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
To date, information on calculating the productivity of excavators used in mining and loading processes at mining enterprises in the Republic of Uzbekistan has been provided. To make the process of calculating the efficiency indicators of excavators understandable, we used pictures of the excavator drawing. Minerals can be selected depending on the parameters of the excavators and the geotechnical location of the mine, and the properties of the rocks being mined in open-pit mining enterprises. If the parameters of the excavator are selected correctly in the mining and loading processes in the mines, the duration of the processes and the economic indicators of the mine will increase.